Passive Shock Isolation Utilising Dry Friction - Mohd Ikmal Ismail; Neil Stuart Ferguson (Shock and Vibration)
A novel shock isolation strategy for base excited system is presented by introducing a two-degree-of-freedom model with passive friction, where the friction is applied to an attached mass instead of directly to the primary isolated mass. The model is evaluated against the benchmark case of single-degree-of-freedom system with friction applied directly to the primary isolated mass. The performances of the models are compared in terms of the maximum displacement response and the acceleration during the application of the shock input for the case when the shock input duration is approximately equal to the natural period of the system (amplification region). From the results, the two-degree-of-freedom model can produce both maximum displacement reduction and smoother acceleration at the point of motion transition. An experimental rig was built to validate the theoretical results against the experimental results; it is found that the experimental results closely match the theoretical predictions.